Program Literasi Digital Untuk Remaja Nagari Talu Dalam Menyongsong Era Teknologi Dan Informasi - Rizalina, Rizalina; Sari, Afni Nia; Sawitri, Elvira (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
This Community Service Program (PKM) is one of the forms of the Tridharma of Higher Education that must be carried out by a lecturer. This PKM is proposed to conduct activities that focus on socialization and education in Nagari Talu. The Digital Literacy Program for the Youth of Nagari Talu aims to improve digital literacy skills among teenagers to face the challenges and opportunities offered by the era of technology and information. In recent years, the rapid development of information technology has had a significant impact on various aspects of life, including education, economy, and socio-culture. Therefore, it is important for teenagers to master adequate digital skills so they can use technology positively and responsibly1. This program is implemented through a series of training and workshops that cover safe internet usage, utilizing social media for educational purposes, and basic information technology skills such as data management and information retrieval. Through this digital literacy program, it is hoped that the youth in Nagari Talu will gain sufficient knowledge and skills to quickly adapt to technological developments, as well as use information technology to improve their quality of life and contribute to the development of their region2.